2007
DOI: 10.1111/j.1538-7836.2007.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fibrinolysis and increased fibrin generation can be detected in hypercoagulable patients using the overall hemostatic potential assay

Abstract: The OHP assay is a simple, inexpensive global test that is useful for assessing patients with hypercoagulable states including APLA. OHP results are significantly abnormal in hypercoagulable groups compared with controls, indicating that both increased fibrin generation and reduced fibrinolysis contribute to hypercoagulable states. The assay may ultimately assist in tailoring clinical management to patients' individual requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 16 publications
2
58
0
1
Order By: Relevance
“…10 Data on links between clot properties and VTE are sparse. Curnow et al 11 showed that hypercoagulable patients with arterial thrombosis or VTE, pregnancy complications, or autoimmune diseases have increased fibrin generation and reduced fibrinolysis. It has been demonstrated that increased D-dimer levels indicating enhanced fibrin formation and degradation represent an independent risk factor for future VTE.…”
Section: Introductionmentioning
confidence: 99%
“…10 Data on links between clot properties and VTE are sparse. Curnow et al 11 showed that hypercoagulable patients with arterial thrombosis or VTE, pregnancy complications, or autoimmune diseases have increased fibrin generation and reduced fibrinolysis. It has been demonstrated that increased D-dimer levels indicating enhanced fibrin formation and degradation represent an independent risk factor for future VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Curnow et al showed that hypercoagulable patients with arterial thrombosis or VTE, pregnancy complications, or autoimmune diseases have increased fibrin generation and reduced fibrinolysis. 131 Several studies documented reduced efficiency of clot lysis in VTE patients. Hypofibrinolysis has been shown in subjects following the first deep-vein thrombosis episode.…”
Section: Vtementioning
confidence: 99%
“…Relationship between the predisposition to intravascular coagulation (thrombophilia) and unsuccessful ART results is actively discussed in current publications; however, mechanisms to produce the impact that increases thrombotic readiness on IVF are not absolutely clear. It is reported that women with thrombophilia may have increased risks for spontaneous abortion, preclinical pregnancy loss and recurrent implantation failure (Christiansen et al, 2006;Coulam et al, 2006b;Curnow et al, 2006;Many et al, 2001;Seghatchian et al, 1996;Stern & Chamley, 2006;Urman et al, 2005;Wichers et al, 2009;Younis et al, 2000). Presently, most studied and prevalent thrombophilias include APS and such risk factors as hereditary antithrombin III deficiency, factor V Leiden mutation, prothrombin mutation, polymorphism of methylenetetrahydrofolate reductase (MTHFR) gene, plasminogen activator inhibitor-1 (PAI-1), fibrinogen, platelet glycoproteins ITGA2, ITGB3, and some others.…”
Section: Data On the Ivf Results As Affected By Pathologies Of Hemostmentioning
confidence: 99%
“…Besides, a number of researchers raise a great interest in the decrease of fibrinolytic blood activity, which is often detected in recurrent miscarriages, APS, deep vein thrombosis of lower extremities, oral contraceptive intake, myocardial infarction, and malignant neoplasms (Bertina, 1997;Birkenfeld et al, 1994;Curnow et al, 2006;Dmowski et al, 1995;Egbase et al, 1999;Lisman et al, 2005;Meltzer et al, 2009;Meltzer et al, 2010;Triplett, 1989;Wichers et al, 2009). The system of fibrinolysis, as well as the system of coagulation, is a complex system which gives characteristics to fibrinolytic responses and its central element that plays role in the activation of plasminogen into plasmin.…”
Section: Data On the Ivf Results As Affected By Pathologies Of Hemostmentioning
confidence: 99%